The Effectiveness of Used Snakes and Ladders Game Learning Media for Review Chinese Vocabulary at Grade 4 Nation Star Academy Elementary School Surabaya - Churota'ayun, Elisa; Yanggah, Minny Elisa; Hezelina, Rachel (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
Chinese language is being learnt as a subject at the school. In Indonesia, there are many schools whom have already begun to get the students used to learning Chinese language one of them is Nation Star Academy Elementary School. There are some problems that students faced while learning Chinese language. The most common problem is memorize characters, make sentences, do not understand the contents of the reading, etc. If the teachers can choose and apply the right teaching method and attract students to learn Chinese language, so learning Chinese language will be easier. In this research, describes how the level of effectiveness of using snakes and ladders game media learning for review Chinese vocabulary at students grade 4 Nation Star Academy Elementary School Surabaya. By using this type of quantitative research experimental method, The form of the design uses a pre-test and post-test one group design and the results showed that learning using snakes and ladders game media in review Chinese vocabulary is considered more effective in improving the learning outcomes of students grade 4 at SD Nation Star Academy Surabaya.